Pemeliharaan Karyawan Dalam Manajemen Sumber Daya Manusia (The Employee Maintenance in The Human Resource Management) - (Jurusan Teknik Elektro Politeknik Negeri Semarang), Sugijono (Teknis, 2015)
The employee maintenance in human resource management (HRM) is an effort either to raise or to maintain physically and mentally the employee condition and attitude in order to be always loyal and to carry out the job productively for supporting the achievement of the company objectives. Thereby great attention must be seriously given to the employee maintenance, since less attention will consequently decrease the working motivation, attitude, loyalty, discipline, and will also increase the absence and the turnover, so that will weaken in supporting the achievement of the company objectives. The success of a company in achieving its objectives is strongly determined by the existence of the employee, so that is required to always keep up the guard and the maintainance of the employee in order to make them feel comfortable, constantly endure, and do the job well. The employee maintenance can be implemented effectively when based on the benefit and efficiency, the need and satisfaction, the equity and fairness, the legal regulation, and the company capability. Some methods in implementing the employee maintenance are such as the two-way communication, the incentive reward, the employee benefit, the safety and health insurance, and the industrial relation..Keywords: employee maintenance, management, human resource.